Analisis Pelayanan Penerbitan Surat Izin Berlayar Di Pelabuhan Untia - Ilham Ashari; Andi Hasmawati; Sufriyadi (Hengkara Majaya, 2020)
This study describes the service of issuing a sailing permit at Untia Port. The data used are primary data obtained from the observation process as well as several community was in the very satisfied category with a percentage of 77.8% while the satisfied category was 22.2%. This requires a wise, detailed explanation, fostering, directing and persuading to respond to all forms of procedures and work mechanisms that apply in a company, so that the form of service gets a positive response. The reliability of the services provided by administrative officers is in the very satisfied category with a percentage of 66.7% while the satisfied category is 33.3%. Good service, hospitality, courtesy, punctuality, and speed in service delivery are important values expected by the community. This is in accordance with the results of the punctuality data provided by the officers in the very satisfied category with a percentage of 75% while the satisfaction category is 25%. The results of the research based on speed/response of administrative officers were in the very satisfied category with a percentage of 75% while 25% satisfied category from 36 respondents said that on average they were very satisfied with the administrative services provided by the harbormaster at Untia Port.